Serum manganese and its association with non-alcoholic fatty liver disease: findings from NHANES - He, Zipeng; Zhao, Yanrui; Tang, Hua (Frontiers in Nutrition, 2025)
ObjectiveThis study examines the link between serum manganese (Mn) levels and non-alcoholic fatty liver disease (NAFLD), with a focus on gender differences.MethodsUtilizing data from the NHANES 2017–2018, we included participants aged 18 and older, excluding those without ultrasonic liver assessment, serum Mn data, or with hepatitis or significant alcohol use. The final analysis comprised 4,294 individuals, with 2,708 in the NAFLD group and 1,586 in the non-NAFLD group. Serum Mn was quantified via inductively coupled plasma mass spectrometry. We compared demographic and health-related variables between groups using appropriate statistical tests and categorized participants into quartiles based on Mn levels. Multivariate logistic regression and spline regression analyses were conducted to evaluate the association between serum Mn and NAFLD risk by gender.ResultsSerum Mn was significantly elevated in the NAFLD group compared to non-NAFLD individuals (9.06 vs. 9.33 μg/L, Z = 2.815, p = 0.005). After adjustments, males in the third Mn quartile showed a higher NAFLD risk (OR = 1.575; 95% CI: 1.193–2.087), while females in the fourth quartile also had increased risk (OR = 1.725; 95% CI: 1.313–2.269), both compared to the first quartile (p < 0.01). A positive dose–response relationship was found for both genders (P for trend <0.01), with nonlinear associations in males (P for nonlinearity <0.01) and linear associations in females (P for nonlinearity = 0.818). Significant interactions with ethnicity in males and hypertension in females were also noted.ConclusionHigher serum Mn levels are significantly associated with increased NAFLD risk in both genders, highlighting the need for gender-specific considerations in future studies and clinical practices.